Blood pressure in head-injured patients. Issue 4 (30th November 2006) - Mitchell, Patrick; Gregson, Barbara A; Piper, Ian; Citerio, Giuseppe; Mendelow, A David; Chambers, Iain R
Abstract : Objective: To determine the statistical characteristics of blood pressure (BP) readings from a large number of head-injured patients. Methods: The BrainIT group has collected high time-resolution physiological and clinical data from head-injured patients who require intracranial pressure (ICP) monitoring. The statistical features of this dataset of BP measurements with time resolution of 1 min from 200 patients is examined. The distributions of BP measurements and their relationship with simultaneous ICP measurements are described. Results: The distributions of mean, systolic and diastolic readings are close to normal with modest skewing towards higher values. There is a trend towards an increase in blood pressure with advancing age, but this is not significant. Simultaneous blood pressure and ICP values suggest a triphasic relationship with a BP rising at 0.28 mm Hg/mm Hg of ICP, for ICP up to 32 mm Hg, and 0.9 mm Hg/mm Hg of ICP for ICP from 33 to 55 mm Hg, and falling sharply with rising ICP for ICP >55 mm Hg. Conclusions: Patients with head injury appear to have a near normal distribution of blood pressure readings that are skewed towards higher values. The relationship between BP and ICP may be triphasic.